PERANCANGAN 2D SISTEM EGD SEBAGAI UPAYA PENINGKATAN EFEKTIVITAS WAYFINDING DAN SIGNAGE PADA KAWASAN KANTIN PUSAT ITS - Ni Wayan Ayu Alvita Wisnawa; Jeanette Eileen Widjaja; Azzam Aulia Trihatmo; Rizki Raditya; Nugrahardi Ramadhani (Kartala, 2023)
The ITS Central Canteen is one of the facilities for ITS students and the general public which is located on Jalan Mechanical Engineering ITS no. 173, Keputih, Sukolilo District, Surabaya City. After being closed due to COVID-19, the ITS Canteen was reopened with updates to improve quality and ensure student comfort. One of the updates is Signage & Wayfinding which is used as a guide to help users achieve their goals, not only that they can be used to increase the design value and aesthetics of the place used. The ITS canteen has provided a form of signage & wayfinding which is estimated to be sufficient for students' needs, but there are obstacles that are felt not only by students but also by ITS canteen management as example, such as complaints regarding directions to the toilet area, use of the reservation room, and regulations regarding the obligation to tidy up the table after used. This study aims to provide the right signage & wayfinding strategy so that it can function and is attractive to look at. The methods used to obtain appropriate data are observation, interviews and documentation. By visiting the location directly, you can do these three methods easily.